Alfacalcidol in prevention and treatment of osteoporosis of endocrine genesis in children and adolescents - V. V. Smirnov; S. A. Miroshnichenko (Лечащий Врач, 2021)
Alfacalcidol is an active synthetic preparation of vitamin D, characterized by high bioavailability and broad pharmacological properties. The article substantiates the possibility of widespread use of alfacalcidol in children and adolescents with osteoporosis of endocrine genesis.